The determinants of church attendance and religious human capital in Germany : evidence from panel data - Guido Heineck (Deutsches Institut für Wirtschaftsforschung (DIW), 2001)
This paper explores determinants of church attendance and the formation of 'religious human capital' in Germany within a Becker-style allocation-of-time framework. The analysis is based on data derived from the German Socio-Economic Panel (GSOEP). Taking advantage of the longitudinal structure of the data, we are able to control for unobservable heterogeneity by applying a random-effects ordered probit model to estimate separate attendance equations as well as 'faith intensity' equations for males and females. The results suggest support for previous findings based on British and North American data that age is a strong predictor for church attendance. Economic variables only weakly account for some of the variation inasmuch as high non-labour income releases time that can be devoted to religious activities. Results for differences in partnership status point to the complementary character of religious experience, whereas the findings for spouses with different religions are more ambiguous. Having at hand a presumably unique situation in the regional structure of religious traditions, we find, not too surprisingly, that strength of belief is much lower in the formerly atheistic East Germany. It is however not clear-cut that North-South or Protestant-Catholic divides exist in religious participation.
Keywords: Z12; J29; D12; 330; Religious behaviour; allocation of time; random-effects ordered probit model; Religion; Kirche; Konsumentenverhalten; Zeitallokation; Humankapital; Schätzung; Deutschland